Micro-polyethylene particles reduce the toxicity of nano zinc oxide in marine microalgae by adsorption. (1st December 2021) - Li, Jiji; Mao, Shuai; Ye, Yingying; Lü, Jiayin; Jing, Fei; Guo, Yahong; Liu, Hongxia; Wang, Ping; Ma, Wei; Qi, Pengzhi; Zheng, Jialang; Qu, Chengkai
Abstract: Contaminant adsorption by microplastics (MPs) allows them to act as contaminant vehicles or vectors, complicating eco-toxicological study of MPs. The contaminants adsorbed are mainly organic contaminants, especially hydrophobic organic contaminants (HOCs), although heavy-metal adsorption has also been reported. Compared to the mechanisms of HOC adsorption, those for metals are not fully understood. In the present study, combined-exposure assays revealed that polyethylene microplastics (PEMPs, 150 μm) alleviate the toxic effect of nano zinc oxide (nZnO, 20–30 nm) on marine microalgal growth by 14.4%. Thus, we hypothesized that nZnO adsorption onto PEMP surfaces ameliorates its toxicity to microorganisms. To test this hypothesis, PEMP samples isolated from nZnO suspensions were characterized. Their surfaces were observed by SEM, their Zn levels were measured by ICP-MS, and the compound form of Zn on the PEMP surface was determined by XRD analysis. The results indicated that 5.53%–7.16% of the Zn in the suspension is adsorbed during the first 24 h of exposure and that the Zn remains as the ZnO form upon adsorption. The findings in the present study provide important information on the role of MPs as metal oxide vehicles. Graphical abstract: Image 1 Highlights: PEMP reduces the toxic effects of nZnO on microalgal growth. An MP size of 100 μm is the dividing point between alleviation and multiple effects. Less than 10% of Zn in a suspension is adsorbed by PEMP. The crystal form of Zn adsorbed on the PEMP surface is that of ZnO.